Identification of novel HNF1B mRNA splicing variants and their qualitative and semi-quantitative profile in selected healthy and tumour tissues - Hojny, Jan (Sci Rep, 2020)
Hepatocyte nuclear factor-1-beta (HNF1B) is a transcription factor crucial for the development of several tissues, and a promising biomarker of certain solid tumours. Thus far, two HNF1B alternative splicing variants (ASVs) have been described, however, the complete spectrum, prevalence and role of HNF1B ASVs in tumorigenesis are unclear. Considering the equivocal data about HNF1B ASVs and expression presented in literature, our aim was to characterize the spectrum of HNF1B mRNA splicing variants across different tissues. Here, we characterize HNF1B ASVs with high sensitivity in carcinomas of the uterine corpus, large intestine, kidney, pancreas, and prostate, with selected paired healthy tissues, using the previously described multiplex PCR and NGS approach. We identified 45 ASVs, of which 43 were novel. The spectrum and relative quantity of expressed ASVs mRNA differed among the analysed tissue types. Two known (3p, Δ7_8) and two novel (Δ7, Δ8) ASVs with unknown biological functions were detected in all the analysed tissues in a higher proportion. Our study reveals the wide spectrum of HNF1B ASVs in selected tissues. Characterization of the HNF1B ASVs is an important prerequisite for further expression studies to delineate the HNF1B splicing pattern, potential ASVs functional impact, and eventual refinement of HNF1B’s biomarker role.